Epidemiology of Mycobacterium tuberculosis complex infections in cattle and humans in the remote pastoral settings of southern Ethiopia - Mohammed, Temesgen; Desta, Fekadu; Wondale, Biniam; Zewude, Aboma; Mamo, Gezahegne; Khalifa, Hazim O.; Bayissa, Berecha; Ameni, Gobena (Frontiers in Veterinary Science, 2025)
IntroductionMycobacterium tuberculosis complex (MTBC) infections are characterized by the development of granulomatous lesions in different parts of the bodies of animals and humans. MTBC infections cause significant economic and public health consequences in Ethiopia. However, there is a shortage of epidemiological data on MTBC infections in the pastoral regions of the country. The objective of the present study was to investigate the epidemiology of MTBC infections in cattle and humans in the remote pastoral setting of southern Ethiopia.MethodsA cross-sectional study design was used to recruit 2,396 cattle and 1,200 human presumptive tuberculosis (TB) cases for this study from the southern pastoral districts of Ethiopia. The single intradermal comparative cervical tuberculin test (SICCTT) was used to screen for bovine TB in the cattle, while mycobacterial culture and spoligotyping were used to identify mycobacterial species and strains in the pastoralists.ResultsThe herd and animal prevalences of bovine TB were 14.9% [95% confidence interval (CI) = 10.2–19.5%] and 3.2% (95% CI: 2.5–4.0), respectively. The herd prevalence was associated with the districts (χ2 = 40.10, p < 0.001). Based on the multivariable binary logistic regression analysis, the male animals were 1.77 (95% CI: 1.02–3.05) times more likely to be TB positive than the female animals. Similarly, the cattle kept in the Dasenech and Benetsemi districts were 10.65 (95% CI: 2.47–45.87) and 22.94 (95% CI: 5.48–95.94) times more likely to be TB positive than the cattle kept in the Selamago district, respectively. Mycobacterial culture positivity was 13.4%, while spoligotyping identified Euro-American (EA), East African-Indian (EAI), Indo-Oceanic (IO), lineage 7, M. bovis, and M. africanum as the major lineages, with proportions of 67.3% (105/156), 22.4% (35/156), 6.4% (10/156), 1.9% (3/156), 1.3% (2/156), and 0.6% (1/156), respectively.ConclusionIn general, the prevalence of bovine TB was relatively lower than that recorded in intensive dairy farms in central Ethiopia. Three species of MTBC, namely M. tuberculosis, M. africanum, and M. bovis, were isolated from the pastoralists of southern Ethiopia. The isolation of M. bovis from the pastoralists could suggest its zoonotic transmission from cattle to humans.